Examining employees level of happiness in relation to productivity in oil and gas industry Abu Dhabi, UAE - Al Hammadi, Naser Yassin (2020)
Employee happiness has increasingly become a vital in oil and gas industries. When people are happy, they tend to work better, they stay at their jobs and also they produce better quality results than the unhappy employees. The United Arab Emirates (UAE) is seventh among the largest natural resource in the world and seventeenth-largest natural gas reserve. In recent years, industries including oil and gas experienced economic challenges brought about by changes happening in the world market. Consequently, the level of happiness of the employees may somehow be affected. Happiness is a necessity for any high-functioning workplace not only oil and gas industr\ pose a great challenge towards happiness of emplo\ees. Stud\ on emplo\ees¶ happiness has recently gained much attention due to its importance on organizational studies and the effect it has on overall performance of the employee, but in oil and gas industry, it is still not fully explored. This research aims to investigate and critically assess domain factors that affects happiness of employees in the oil and gas industry in Abu Dhabi, UAE. In addition, this study intends to examine the relationship between level of happiness and productivity in the said sector according to the demographic profile of the respondents. A survey used to gather data results from present employees of Abu Dhabi National Oil Company (ADNOC), one of the largest suppliers of oil all over the world. Results are calculated using IBM Statistical Package for the Social Sciences (SPSS) reveals that there is a significant relationship on the level happiness of oil and gas industry employees in relations to productivity in Abu Dhabi, UAE when grouped according to profile. The outcome of the study aims to help improve one¶s job for the betterment of performance and productivity level in an oil and gas industry and determine what satisf\ an emplo\ee due to happiness in one¶s career and profession.